Frequency and Causes of Fracture of Acrylic Resin Complete Dentures in Edentulous patients - Javeria Iftikhar, Muhammad Nasir Saleem, Faiza Awais, Ayesha Naz, Adeel Tuasene, Zain Saleem, Khezran Qamar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The rehabilitation of edentulous patients requires acrylic resin complete dentures to fulfil their functional and esthetic needs. Fractures of dentures are one of the commonest complaints around the world. Aim: To evaluate the frequency of acrylic complete denture fractures among edentulous patients and find out their association with certain variables. Methodology: A cross sectional observational study was carried out in Prosthodontic department of Lahore Medical and Dental College, Lahore from 26th March 2020 to 26th September 2021. A total of 58 completely edentulous patients reported with fractured acrylic dentures were selected. Patients were evaluated both intra and extra orally to find out the cause and site of fracture. Various parameters namely, denture age, fracture sites, gender were statistically evaluated to find out their relationship with denture fracture. Results: Results showed that male patients; 56.9% were presenting more with fractured dentures than female; 43.10%. In males the midline denture fractures were most commonly seen 45.5%, whereas in females’ fracture at premolar area was commonly observed 28.0% however no statistical dependance between fractured dentures sites and gender was found. Denture fractures were most prevalent in mandibular arch 50% as compared to maxillary 39.7%. Mid line fracture was the commonest site observed in both maxillary 30.4% and mandibular arches 31.0%. Insignificant association between fracture sites and dental arches was seen. Maximum denture fractures were recorded in first 2 years of denture fabrication 55.2%. The most frequent cause of denture fracture was accidental falling 34.5%. Conclusion: The frequency of complete denture fracture is more in mandible as compared to maxilla and the main reason is patients’ negligence. The study also showed midline fracture of dentures to be the most frequent site of denture fracture. Keywords: Acrylic dentures, Complete dentures, Edentulism, Edentulous, Prosthesis, Tooth loss,